Independence From Parenteral Nutrition and Intravenous Fluid Support During Treatment With Teduglutide Among Patients With Intestinal Failure Associated With Short Bowel Syndrome. (August 2017) - Iyer, Kishore R.; Kunecki, Marek; Boullata, Joseph I.; Fujioka, Ken; Joly, Francisca; Gabe, Simon; Pape, Ulrich-Frank; Schneider, Stéphane M.; Virgili Casas, María Nuria; Ziegler, Thomas R.; Li, Benjamin; Youssef, Nader N.; et al.
Background: In phase III clinical studies, treatment with teduglutide was associated with clinically meaningful reductions (≥20% from baseline) in parenteral support (PS; parenteral nutrition and/or intravenous fluids) requirements in adult patients with intestinal failure associated with short bowel syndrome (SBS-IF). This analysis reports clinical characteristics of patients who achieved complete independence from PS during teduglutide treatment. Materials and Methods: Post hoc analysis of adult patients who achieved complete PS independence during treatment with teduglutide 0.05 mg/kg/d. Data were pooled from 5 teduglutide clinical trials (2 phase III placebo-controlled trials [NCT00081458 and NCT00798967] and their respective extension studies [NCT00172185, NCT00930644, NCT01560403]). Descriptive statistics were used; no between-group comparisons were performed because of the small sample size and lack of comparator. Results: Of 134 patients, 16 gained oral or enteral autonomy after a median of 5 years of PS dependence and 89 weeks of teduglutide treatment. Demographic and baseline disease characteristics varied among patients (median age, 55 years; 50% men; median baseline PS volume, 5.1 L/wk; median residual small intestine length, 52.5 cm). Most patients who achieved PS independence had colon-in-continuity; however, there was no significant difference in the frequency of PS independence among patients who maintained colon-in-continuity vs those who did not. Conclusion: Findings from this post hoc analysis suggest that oral or enteral autonomy is possible for some patients with SBS-IF who are treated with teduglutide, regardless of baseline characteristics and despite long-term PS dependence.